Biological Sensing Using Vertical MoS2-Graphene Heterostructure-Based Field-Effect Transistor Biosensors - Ying Chen; Nataly Vicente; Tung Pham; Ashok Mulchandani (Biosensors)
Our study develops two configurations of MoS2 and graphene heterostructures—MoS2 on graphene (MG) and graphene on MoS2 (GM)—to investigate biomolecule sensing in field-effect transistor (FET) biosensors. Leveraging MoS2 and graphene’s distinctive properties, we employ specialized functionalization techniques for each configuration: graphene with MoS2 on top uses a silane-based method with triethoxysilylbutyraldehyde (TESBA), and MoS2 with graphene on top utilizes 1-pyrenebutyric acid N-hydroxysuccinimide ester (PBASE). Our research explores the application of MoS2–Graphene heterostructures in biosensors, emphasizing the roles of synthesis, fabrication, and material functionalization in optimizing sensor performance. Through our experimental investigations, we have observed that doping MoS2 and graphene leads to noticeable changes in the Raman spectrum and shifts in transfer curves. Techniques such as XPS, Raman, and AFM have successfully confirmed the biofunctionalization. Transfer curves were instrumental in characterizing the biosensing performance, revealing that GM configurations exhibit higher sensitivity and a lower limit of detection (LOD) compared to MG configurations. We demonstrate that GM heterostructures offer superior sensitivity and specificity in biosensing, highlighting their significant potential to advance biosensor technologies. This research contributes to the field by detailing the creation process of vertical MoS2–graphene heterostructures and evaluating their effectiveness in accurate biomolecule detection, advancing biosensing technology.